Enhancing Reading Instruction through Multimodality: A Pathway to Success - hidayah nor; Amaliya Septiani (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2023)
This qualitative study investigates the use of multimodality in teaching reading to junior high school students at SMPN 1 Pulau Laut Tengah Kotabaru. Multimodality refers to the integration of various modes, such as images, sound, and writing, to convey meaning and enhance the learning process. The research involves one English teachers and 24 eighth-grade students as participants. The researchers used Descriptive qualitative as the research methods. In addition, observation, interviews, and documentation were utilized as data collection instruments. The findings reveal that teachers frequently employ multimodality, particularly in English reading lessons, utilizing a combination of digital and printed resources such as videos and images to engage students actively in the learning process. The application of multimodality in teaching reading yielded positive responses from students, fostering enthusiasm and improving their participation in learning activities.